MicroRNA‐125a promotes resistance to BRAF inhibitors through suppression of the intrinsic apoptotic pathway. (19th April 2017) - Koetz‐Ploch, Lisa; Hanniford, Douglas; Dolgalev, Igor; Sokolova, Elena; Zhong, Judy; Díaz‐Martínez, Marta; Bernstein, Emily; Darvishian, Farbod; Flaherty, Keith T.; Chapman, Paul B.; Tawbi, Hussein; Hernando, Eva
Summary: Melanoma patients with BRAF V 600E ‐ mutant tumors display striking responses to BRAF inhibitors (BRAFi); however, almost all invariably relapse with drug‐resistant disease. Here, we report that microRNA‐125a ( miR‐125a ) expression is upregulated in human melanoma cells and patient tissues upon acquisition of BRAFi resistance. We show that miR‐125a induction confers resistance to BRAF V 600E melanoma cells to BRAFi by directly suppressing pro‐apoptotic components of the intrinsic apoptosis pathway, including BAK1 and MLK3. Apoptotic suppression and prolonged survival favor reactivation of the MAPK and AKT pathways by drug‐resistant melanoma cells. We demonstrate that miR‐125a inhibition suppresses the emergence of resistance to BRAFi and, in a subset of resistant melanoma cell lines, leads to partial drug resensitization. Finally, we show that miR‐125a upregulation is mediated by TGF β signaling. In conclusion, the identification of this novel role for miR‐125a in BRAFi resistance exposes clinically relevant mechanisms of melanoma cell survival that can be exploited therapeutically.